PATIENT SATISFACTION WITH DENTAL HEALTH CARE DURING THE COVID-19 OUTBREAK IN SERBIA - Stoiljković, Ivana; Nikolić, Maja; Mitić, Vladimir; Šljivić, Katarina (Sanamed, 2024)
Introduction: The COVID-19 virus belongs to the group of respiratory viruses. Due to the nature of their work, dentists are at greater risk of contracting the new coronavirus during dental interventions. Knowing the path of transmission of the virus is of great importance in preventing and suppressing the development of infection. Patients' fear of infection during the coronavirus pandemic was significant, and because of this, visits to the dentist for standard dental services were postponed, and patients came only for emergencies. Adherence to protective measures directly affected patients' satisfaction with dental services.The aim of this work was to examine patient satisfaction with dental services during the coronavirus pandemic.Materials and Methods: The study was designed as a cross-sectional study using an epidemiological questionnaire. A total of 120 patients were surveyed, 60 from private practice and 60 from the state sector. The questionnaire was anonymous and contained sociodemographic questions and questions related to knowledge of protocols and satisfaction with dental services. The data were processed in the SPSS 11.5 program.Results: Out of 120 respondents with an average age of 38.92 ± 13.08 years, 98% were familiar with the protocol for protection against the coronavirus. There were no dissatisfied people in either private practice or the public sector; the only difference was in the degree of satisfaction. In private practice, more respondents were very satisfied as the highest level of satisfaction, while in the public sector, it was very satisfied. Conclusion: A good knowledge of the protocol for protection and prevention of the spread of the virus raises awareness among dentists and patients. By following these measures, infection with the virus is reduced to a minimum, and therefore patient satisfaction with dental services is at a higher level.
Keywords: COVID-19; patient satisfaction; dentistry